(untitled) - SEHILING, YESI (Language Horizon: Journal of Language Studies, 2014)
10The Students’ Attitudes Toward the Instructor’s Code Switching in EFL Classroom Yesi Sehiling S1 Sastra Inggris, Fakultas Bahasa dan Seni Universitas Negeri Surabaya, Indonesia yesisehiling@gmail.com Abstract English has a big influence in the world. It can be seen that almost all of the country around the world put English as one of the foreign language which is taught in any level of the institutions. In Indonesia, English is taught from kindergarten until university level which is called as English as Foreign language. It is because the awareness that almost information around the world is provided in English, which is the key to make the generation moves forward following modern era.Because English is a foreign language, it may be hard to be learned to Indonesian society. So, to make it interesting, English should be delivered as enjoyable as possible and in the right way so that the learner can get the English learning well. Teaching English in Indonesia is usually delivered in English. But, there are some instructors sometimes use Indonesian to switch the code from English when teaching in the classroom. This study focuses on the use of code switching by the instructor and the students’ attitudes toward the teacher’s code switching in EFL clasroom. In fact, the researcher would like to know whether the language choice in teaching EFL classroom may influences the students’ attitudes toward the language or not. This study used qualitative approach. The instruments which are used are some notes, video recorder and the researcher itself. To collect the data, this study uses observation, interview and questionnaire. The Objects of the study are in EFL classrooms (senior high school, English department and Indonesian department). The subjects of the study are the English teacher and the students. The findings of the study show that the use of code switching may be as simply talks and within any reason and perpose. The further findings indicate that the students’ attitudes toward code switching by the instructor are largely influenced by the students’ English proficiency. The less proficient students preferred the instructor to use both language which English should be minimized and Indonesian more explored. The more proficient students preferred the instructor to minimize the use of code switching if it is not needed enough and more explore English. Keywords: code switching, attitude, language attitude, EFL. Introduction Language is the most important thing for human life. By using language, the people can express their thought and sense to others (Humaidah, 2009: 2). But the most main function of language (Whatmough, 1957 :12) is to communicate each other. Communication is a kind of interaction which uses code that must be dealt by the speaker and the listener. If between the deliverer and the interlocutor does not know their code each other, their communication means nothing. Even though what they deliver consist some information, they will not be able to get what information is. In global world, people are obligated to be bilingual or multilingual which international language is included. It aims to make the people are able to interact with all the people around the world. Besides, all the world information must be provided in International language. By being able to understand International language, the people can access the information. English is an international language. It has a big influence. Almost all the countries in the world learn English. Indonesia does too. English is an important subject of school in Indonesia. It is taught in any level of school started from kindergarten, elementary school, junior high school, senior high school and university. It is hoped that the availability of English language as the subject of their school can contribute to the students’ English language competence, which is the key to access information in the world. Besides, learning English aims that they are able to communicate using international language and have relation in international world considering international relationship is very important for life. In Indonesia, English is most taught as foreign language in formal setting. They are put in the classroom where the learning takes place. In this situation, the classroom is called as EFL (English as Foreign Language) classroom considering that Indonesia is non-English speaking country. According to Yletyinen (2004: 4), in EFL classroom, the learner learns English in an environment where there is only a little natural use of the language. Furthermore, the foreign language is treated equally to the other subjects with its homework and test. In EFL classroom in Indonesia, the teacher teaches the students English in order to make the students understand English by listening, reading, doing written and oral activities. The language of teaching is usually English. However, there are teachers sometimes change from English to Indonesian and vice versa in delivering the subject. This phenomenon is called as code switching. Code switching is very common in bilingual and multilingual societies. Wardhaugh (2006: 101) says that code switching is changing of codes from one code to another code or to mix the code in the same conversation. In the other words, code switching is the use of two or more languages in the same conversation. The code switching usage (Uys, 2000: 2) by the teacher in the class may have any reason or purpose such as the teacher uses code switching as strategy (Yletyinen, 2004: 53; Uys, 2000: 11) to explain in order to make the students understand what she/he has told or may be because she/he has less competence (Yletyinen, 2004: 72) in speaking English so she/he uses much Indonesian. This problem is very interesting topic to be discussed in this study especially related to student’s attitude toward this phenomenon. Attitude is something that is got by the people through interaction with an object or accident. Attitude is not brought since baby but it is created through learning process in environment. There are factors that can change someone’s attitude that are feeling, knowledge, experience and motive. Language is also related to attitude. Attitude toward language is called as language attitude. Language attitude is someone’s attitude in choosing and deciding which language to be used. Language attitude is quite influenced by background and something happen in the environment. The students of Senior High School are in the high level of learning in school world under university students. They are expected to have good English skill after they graduate. In this case, the way of teaching them must also different from the previous grade. The capacity of using English rather than Indonesian of the teacher must influence the student’s ability of English especially in speaking. In simply, using code switching by the teacher whether it is favored or disfavored by the students is focused in this study. There are earlier studies related to this paper done by Yletyinen (2004) which is titled the function of code switching in EFL Classrom. Then, Arrifin and Husin (2011) which is titled Code Switching and Code Mixing of English and Bahasa Malaysia in Content-Based Classroom and Alenezi (2010) which is titled Students’ Language attitude Towards Using Code Switching as a Medium of Instruction in the College of Health Sciences: An Exploratory Study. Both of the studies analyze the language attitude towards code switching as a medium of instruction. The present study focused on the situation of code switching which is used by the teacher in the classroom and the student’s attitude toward code switching by the instructor too. Research Question This research is guided by the following questions: Under what situation does the teacher use code switching in the classroom? How do the students take attitudes toward the teacher’s code switching in the classroom? Purpose of the Study Related to the background of the study and the research question, the purposes of the study are: Describe the situation of the instructor’s code switching in the classroom. Describe the students’ attitudes toward the instructor’s code switching. Significance of The Study The result of the study is hoped that can give contribution to sociolinguistics especially in the term of code switching and the attitudes toward code switching. But the most contribution may be for the teacher who teach EFL classroom in guiding the class to optimize positive attitude of the students toward English to get the better result of students’ competence. Moreover, this study can give description to the people who will have research as this present study. Method Research method is the most important part of a research because it shows how the study is organized. This study uses qualitative method. Qualitative method is research procedure that produces descriptive data in the form of written words from the people or attitude that can be researched. This chapter consists of research design, subject, object, and the location, sources of the data, data collection techniques, instruments and data analysis. Research Design This study uses descriptive qualitative and quantitative data. According to Bodgan and Taylor on Margana’s Disertasi (2012), descriptive qualitative uses data in the form of word, phrase, or clause whether written or spoken which is used to give overview of a certain description of phenomena about code switching. The quantitative data (Litosseliti, 2010: 52) enabless the the researcher to compare relatively large numbers of the students’ attitudes in EFL classroom of the research which is as the main focus of the present study. Objects, subjects and location The objects of the study were classrooms of Senior High School, Indonesian department and English department that Senior High School was the main object and the others were to compare the result of the data. However, not all classrooms of the departments were researched but only one class of each department which was chosen randomly by the instructor. The objects were taken to compare the result considering their different level. Why should those objects be compared? Firstly, Senior High School is the highest level of obligated education program by Indonesian government. After graduating from this level, they were not obligated to continue their education in university. So that’s why, they have to be given good skill in order to be able to get good enough job. It is quite related with their English skill because people who have good English competence and performance will get good/higher position than low English competence one of a company. Secondly, Indonesian department are the higher level of Senior High School. The perception is that the students of Indonesian have higher competence than Senior High School. But they may favor Indonesian rather than English considering their choice to choose Indonesian department rather than English department. Thirdly, English department is the department which the society use most English in their communication in the context of learning. All the students may have good English ability considering their ability to interact each other using English in the class. This object was used to compare and to get more varied data considering the different level and the English competence. The subjects of the study were all the societies in each classroom including the English teacher and the students. In this case, the teachers followed to answer Question 1 and the students followed to answer Question 2. Talking about the location, all of them are in East Java. Senior High School took place in SMA 1 Wonoayu. It is located in Pagerngumbuk village, Wonoayu, Sidoarjo. And, Indonesian department and English department took place in Universitas Negeri Surabaya which is located in Lidah Wetan village, Lakarsantri, Surabaya. Most societies of the institutions are multilingual (Javanese, Indonesian, and English). But, the language which is most used in classroom is Indonesian considering Indonesian is the formal language in Indonesia. However, it is the exception of English subject which English is most used. Moreover, the location takes place around the researcher’s environment that could help the researcher to get the data easier. Data and Sources of Data This present study classifies the data into two types. They are linguistics and information data. The linguistics data is the situation of code switching by the teacher and the students’ attitudes toward the code switching. The information data is obtained when the researcher conducted interview of the instructors about the reason of the use of code switching in the classroom and the interview and questionnaire of the students about the acceptability of the code switching by the instructor. The questions of the interview of the teacher was not listed but developed by each situation in each classroom. In the other hand, the interview of the students were listed which can be seen in Appendix 4 and the questionnaire which is adopted from the Likert scale (Arrifin and Husin, 2011) which was drawn below. No. Statement Strongly Agree Agree Disagree Strongly Disagree There were three kinds of source of data in the present study. They were people, place, and papers. The people were the instructors and the students of the institutions. The place was in the classroom. The papers were from the related theories which were gotten from the books, previous studies and internet. Research Instrument The instrument is used to facilitate and get the data. In this study, the data were collected by direct observation, questionnaire and interview. In doing the research, some tools were used to save the data by using some notes and video recorder. The gotten data is analyzed and related to the theories/previous studies. Question 1 : Under what situation does the instructor use code switching in the classroom? In order to answer question 1, direct observation and interview were used. Interview was used for the teacher to get more information about the reason of using code switching. In the interview activity, it was not made interview sheet because the interview was done directly based on the situation of code switching in each classroom. See Appendix 1,2 and 3 to get more details information. Question 2: How do the students take attitudes toward the teacher’s code switching in the classroom? In order to answer question 2, questionnaire, interview and direct observation were used for the students. Questionnaire sheet was used to answer the Question. The interview and direct observation were also used to strengthen the data. The tools were video recorder. The data from the instrument was analyzed which also needed some theories relating to the study in analyzing the data. However, the researcher was the key instrument to answer those two questions. The researcher as the instrument means that the researcher became the determiner in collecting data. She paid attention, followed, took a note and analyzed the data. Data Collection Technique Data collection technique of this study was done by doing observation, interviewing, and giving questionnaire. Observation Direct observation was used to get the data. It was done to see the phenomenon of code switching by the instructor directly and how the students take attitudes toward the use of code switching by the instructor and to take a note the whole learning activity in the classroom. The direct observation was also video recorded. Interview This study uses spoken interview to collect the data. Both teacher and the students were interviewed. The tool was video recorder. Interview for the teacher (see Appendix 1,2,3) was done after the observation. In contrast, interview for the students (see Appendix 4) was done before the observation. The students who were interviewed was chosen randomly based on their English competence, higher competence and lower competence. The categorization of their English Competence was based on their score. Each instructor has their characteristic of giving score and categorizing the students whether they are less competence or more competence. The teacher of senior high school had requirement that the students who have score under 80, they are categorized as less competence and upper 80 as more competence. The lecturer of English department did say so. Whereas the lecturer of Indonesian department gave score under 70 for less competence and upper 70 for more competent students. Questionnaire Questionnaire was used for the students. There were 8 statements of the questionnaire. The questionnaire was given to all students in the classroom according to their presence when the research was done. Data Analysis In analyzing the data, there are some steps below: The data were classified according to the situation or specific time of the use of code switching by the instructor and the students’ attitudes toward the use of code switching. However, the data collections of the interview were transcribed. The data were then analyzed based on the theories and previous studies. The data were interpreted and made conclusion about the result of the study and also provided some suggestion for the future study by the researcher. Results and Discussion The use of code switching The data reveal a clear pattern of instructor’s language use in the classroom. All of the institutes above showed the use of code switching English-Indonesian or Indonesian-English by the instructor was common practice phenomenon. The characteristics of each institute also influence the frequent of the use code switching or the languages whether the more frequent was English or Indonesian. Senior high school institute used code switching balance whether English-Indonesian or Indonesian-English. It was different with Indonesian department that the institute used more frequent in Indonesian and unaware in using English. On the other side, the lecturer of English department used English more frequent in the classroom and Indonesian was just used in simply talks or just to give more explanation and example. Eventhough the institutes had their own characteristics, here the results of the code switching use in each institute were summerized into one. Those, code switching by the instructors in the classroom happened under situation below: Code switching happened in explaining the material which was used to make the explanation clearer to be understood by the students. According to Yletyinen (2004: 53), there are different strategies for explaining the material being taught by mentioning repetition, reformulation, clarification and exemplification. In the present data, code switching in explaining material is common which was happened in all the institutions whether in senior high school, Indonesian department and English department of university. This result supports Yletyinen’s thesis (2004: 53) and Uys (2000: 44) which they found that the teacher has to clarify his/her message by code switching to the students’ mother tongue and thus making the students more understand the material and do what the teacher asks to do. However, the code switching was most used in the senior high school. Code switching was used as the student’s requirement. This reason of code switching is the same result with Youkhana (2010: 15) that the students tend to ask the teacher to change the code into mother tongue because they discomfort to the English used because it makes them confused to understand the instructor’s speech. Code switching was used in joking. According to Weng, this function of code switching is called as poetic function that the speaker inserted some jokes, stories, some poetic quotation in the conversation. Joking (Uys, 2000: 44) in mother tongue is more understandable and felt rather that in foreign language because mother tongue has stronger role to catch the meaning. This finding is supported by Wardhaugh (2006: 112). He said that code switching can be used for humorous effect. In other words, code switching has purpose of joking. Code switching happened in simply talks which were with unawareness. This phenomenon is often happened. It was found in the three institutes in the research. The code switching was spoken accidentally, since it was not required. According to Yletyinen (2004: 95), this code switching is called lapse. Lapse was most frequent happened in Indonesian department which the instructor delivered her speech most in Indonesian and slipped English words sometimes. It is different with senior high school and English department which are commonly slipped Indonesian words. Code switching was used when the instructor was disappointed with the students. This code switching (Yletyinen: 2004: 89) is called as teacher admonition. She said that the mother tongue sometimes has more power in the foreign language classroom. This is also called as expressive function of code switching (Weng’s article: 4) that the teacher uses code switching to express the emotion and mother tongue is often inserted to express the true feelings. This strategy by the instructor will make the students more alert, they response better to their mother tongue. Furthermore, they know that they do not have an excuse by appealing not to understand the teacher. In this case, code switching used when reprimanding students is the effective strategy. Code switching happened to get the students’ attention. This is named directive function (Weng’s article: 4). In the direct observation, the teacher asked “How many groups that have finished the assignment?” Almost of the students just kept silent. Then, the teacher asked again “berapa banyak group yang sudah menyelesaikan tugasnya?” The students answered the question by raising hands. Implicitly, The use of mother tongue had a purpose that was to get the students attention the teacher’s speech. According to Yletyinen’s thesis (2004: 70), code switching can be used in helping the less competent students to answer a question that the teacher asks. Yletyinen’s statement supports the idea above that the teacher changed the code into Indonesian to help the students who most of them were less competent to understand the teacher’s question and answer it. The use of Indonesian here was also aimed to help the students understand the question so that the students could answer the teacher’s question. Not only that, code switching (Wardhaugh, 2006: 112) that is by choosing the preferred language of the students, the message will be easier to catch. The students’ attitude This study shows that code switching of English and Indonesian is a common communicative behavior in the classrooms. However, this study is aimed to explore students’ attitude towards the language of teaching in English class and the effects of the instructors’ code switching to the students’ English performance. The findings of this study indicate that the students’ attitude toward code switching in the English class was largely influenced by the students’ English language competence. Although in fact, The classrooms had each characteristics which senior high school class was the neutral one which was not in Indonesian department class or English department class. It is because the students commonly more favor the language they took as their majure than another one. The students of Indonesian department showed their favor to Indonesian much and the students of English department showed their favor to English. It was proved by their decision of taking those majure. So, eventhough they were in English subject classroom, they tended to consider their own majure. In the other hand, the students of senior high school take attitudes about code switching that were purely influenced by the students’ English competence. The results show that the students with less proficiency prefer their teacher to use both English and Indonesian in the same capacity or larger use Indonesian. Alenezi (2010: 7) said that the students more desirable and believe that code switching of the teacher makes the course easy to understand. They would get difficulties to catch the meaning of the speech if the instructor used English a lot. Meanwhile the students with higher proficiency prefer their teacher to use more English. The findings are supported by the Arrifin’s and Hussin’s (2011: 237) study that the students with less English proficiency were more tolerant to the instructors’ code switching compared to the more proficient group. The students with higher proficiency might believe that the use of English by the teacher could improve their language competence specifically in vocabulary. Weng’s article also found that it can help the students to understand new vocabulary. The results are rather different in the English department which shows that the students were sometimes confused about the use of code switching by their lecturer that did not add their vocabulary. They believed that for adding vocabulary, it depends on their desire and their effort by reading English books, watching movie and listening the musics. They further argued that the use of code switching should be minimized. The argument was also founded in David’s article (2008: 78) that it should be minimized because it is bad for the learner. It assumed that if the teacher often used that, it can make the bad behavior to the next generation and will be more difficult to avoid. However, all the students agreed that the use of code switching can increase their comprehension toward the lesson. Riegelhaupth (2000: 210) argued that bilinguals use the language that the people they speak to know best. In this case, the use of code switching has function to repeat the speech for better comprehension. The results also showed that code switching by the teacher had each effect to their psychology aspect. The lower proficient students were not confidence to speak English to the teacher who was using code switching. They tended to use Indonesian because they were afraid of making mistakes or troubles to their speaking if they use English. They thought that they had poor vocabulary and poor understanding of grammar. But if the teacher spoke in English, they would try speaking English too then use Indonesian to the words which they did not know the meaning. Different with the lower proficient students, the higher proficient students were still confidence to speak in English to the teacher who was using code switching even though in a simple sentence. However, sometimes, they tended to use Indonesian or code switching because they did not want to be seen showing off their English competence. Again and again, the students of English department had different results. The lecturer’s code switching did not influence their confidence. Whatever language the lecturer used, they were still confident to speak English but sometimes they followed the language the lelcturer used just to respect him. It is supported by Spolsky (1998: 49) that one tends to respect people who are socially superior to one self. Conclusion and Suggestion Conclusion This chapter is summary of the findings in order to make the reader get a better understanding through reading the findings of this thesis. Actually, the main objective of this present study is to investigate the students’ attitude toward the instructor’s code switching behavior in EFL classroom. After doing the research, the results are: The first finding is the situation of code switching phenomena by the instructor which is about the reason or the purpose of using code switching in the classroom that is drawn commonly below: Code switching happened in explaining the material which was used to make the explanation clearer to be understood by the students’ code switching was used as the student’s requirement Code switching was used in joking Code switching happened in simply talks which were with unawareness. Code switching was used as admonition which is used when the instructor was disappointed with the students. Code switching happened to get the students’ attention. There are also additional findings that the instructors’ frequency of using English or the Indonesian is largely influenced by the characteristic of the classroom. Senior high school institute used code switching balance as a mean the same frequency whether English-Indonesian or Indonesian-English. It was different with Indonesian department that the institute used more frequent in Indonesian and unaware in using English. It is influenced by the students’ favor toward Indonesian. On the other side, the lecturer of English department used English more frequent in the classroom and Indonesian was just used in simply talks or just to give more explanation and example. The second finding is the students’ attitude toward the instructor’s code switching in the classroom. The findings of this study indicate that the students’ attitude toward code switching in the English class was largely influenced by the students’ English language competence. Although in fact, The classrooms had each characteristics which senior high school class was the neutral one which was not in Indonesian department class or English department class. It is because the students commonly more favor the language they took as their majure than another one. The students of Indonesian department showed their favor to Indonesian much and the students of English department showed their favor to English. It was proved by their decision of taking those majure. So, eventhough they were in English subject classroom, they tended to consider their own majure. In the other hand, the students of senior high school take attitudes about code switching that were purely influenced by the students’ English competence. The results show that the students with less proficiency prefer their teacher to use both English and Indonesian in the same capacity or larger use Indonesian. They would get difficulties to catch the meaning of the speech if the instructor used English a lot. Meanwhile the students with higher proficiency prefer their teacher to use more English. The students with higher proficiency might believe that the use of English by the teacher could improve their language competence specifically in vocabulary. The results are rather different in the English department which shows that the students were sometimes confused about the use of code switching by their lecturer that did not add their vocabulary. They believed that for adding vocabulary, it depends on their desire and their effort by reading English books, watching movie and listening the musics. The findings also showed that code switching by the teacher had each effect to their psychology aspect. The lower proficient students were not confidence to speak English to the teacher who was using code switching. They tended to use Indonesian because they were afraid of making mistakes or troubles to their speaking if they use English. They thought that they had poor vocabulary and poor understanding of grammar. But if the teacher spoke in English, they would try speaking English too then use Indonesian to the words which they did not know the meaning. Different with the lower proficient students, the higher proficient students were still confidence to speak in English to the teacher who was using code switching even though in a simple sentence. However, sometimes, they tended to use Indonesian or code switching because they did not want to be seen showing off their English competence. Again and again, the students of English department had different results. The lecturer’s code switching did not influence their confidence. Whatever language the lecturer used, they were still confident to speak English but sometimes they followed the language the lelcturer used just to respect him. Suggestion The instructor in EFL classroom should know the students’ attitude toward the language used well so that she/he can use the right way in teaching English in EFL classroom in order to get the best result of the students’ English competence. This study may be far from being perfect. It is hoped that there will be further researchers who conduct the research on the phenomenon of code switching by the instructor in the classroom and the students’ attitude toward it for more detail data/explanation and from many points of view. References Alenezi, Abdullah. (2010). Students’ Language Attitude Towards Using Code-Switching as a Medium of Instruction in the College of Health Sciences: An Exploratory Study, vol.7, 1-22 Arrifin, Kamisah and Husin, MisyanaSusanti. (2011). “Code Switching and Code Mixing of English and Bahasa Malaysia in Content Based Classrooms: Frequency and Attitudes”.The Linguistics Journal.Vol 5 issue 1 David. (Desember, 2008).Understanding Mixed Code and Classroom Code-Switching: Myths and Realities. Ongkong Institute of Education.Hongkong.Vol 56, No.3 Faris, NurulElfatul. 2012. Alih Kode Dalam Proses Belajar-MengajarKelas VII Mts “AL-KAutsar” Srono Banyuwangi.UniversitasJember, Jember. Gardner-Chloros, Penelope. 2009. Code Switching. UK: Cambridge University Press. Litosseteliti, Lia. 2010. Research Methods in Linguistics. New York: Continuum. Riegelhaupth, Florencia. 2000. Code Switching and Language Use in the Classroom. Research on Spanish in the U.S., ed. Ana Roca, 204-217. Somerville,MA: Cascadilla Press. Spolsky, Bernard. 1998. Sociolinguistics. UK: Oxford University Press. Uys, David. 2010. The functions of teachers’ code switching in multilingual and multicultural high school classrooms in the Siyanda District of the Northern Cape Province: Stellenbosch University. Wardahugh, Ronald. 2006. An Introduction to Sociolinguistics. UK: Blackwell Publishing. Wardani, Devi. (2013), Skapbahasasiswaterhadapbahasa Indonesia: studikasus di SMA Negeri 1 Singaraja. E-Journal Program Pascasarjana Universitas Pendidikan Ganesha, Vol. 2 Weng, Pei-shi. Code Switching as a Strategy Use in an EFL Classroom in Taiwan.Tamkang University, Taiwan. Whatmough, Joshua. 1957. Language: A Modern Synthesis. New York: St. Martin’s Press. Yletyinen, Hanna. 2004. The functions of code switching in EFL classroom. University of Jvyoskyl: Finland. Youkhana, Sana. 2010. Code Switching in the Foreign Language Classroom. Ogskolan: Jonkoping.